Cultural Heritage and Educational Innovation: A Study on the Integration of Traditional Music Culture in Vocal Music Education - He, Xuan (Journal of Educational Theory and Practice, 2026)
Considering the current processes of globalization along with the fast development of information technologies, music education faces certain difficulties and challenges as well as opportunities. In this regard, this article studies the problem of the use of the traditional musical culture for the purposes of vocal music education by considering the relation between the vocal music art and culture through systematizing this relationship. At the same time, the research considers the problem of semiotic approach in vocal music education and reveals the features of cultural features of traditional vocal music art. The present work proposes a new model of the development of vocal music education based on the following key approaches such as the return to its cultural origin, traditional humanistic spirit, and consideration of multicultural views on life. Furthermore, the use of modern technologies in vocal music education is also discussed. Among other things, the integration of computer and multimedia technologies in vocal music teaching is considered. Consequently, the results of the research show that the use of the traditional musical culture in the field of vocal music art leads to greater success in vocal music education in terms of cultural and professional progress.